You are on page 1of 14

STRONG MATHEMATICAL INDUCTION Lecture No 2.

(PROVING, VALIDATION AND VERIFICATION, ETC.)


Proof: Generalized Demargon’s Law by Induction
( A  A ...  A = A  A  ...  A )
n n
Prove  Aj =  Aj when n2, i.e., 1 2 n 1 2 k
j =1
j =1

Proof
( )
Basis step: Since, A1  A2 = A1  A2 true for n = 2
Induction step: Assume the result is true n = k and then prove for n = k+1.

k +1 k
 A j =  A j  Ak +1
j =1 j =1
k
=  A j  Ak +1
j =1
k
=  A j  Ak +1 (by induction hypothesis )
j =1
k +1
=  Aj
j =1
Base case n=2
2 2
 Aj =  Aj
j =1
j =1

(A  A 1 2 = A1  A2 )
Inductive Step
n=k
k k
 Aj =  Aj
j =1
j =1

( A  A  ...  A
1 2 k = A1  A2  ...  Ak )
n = k +1
k +1 k
 Aj =  Aj  Ak +1
j =1 j =1

( A  A  ...  A  A )
1 2 k k +1
Postage Ticket: Again More Steps in Basis
Prove that postage ticket of amount  12 cents can be formed
using only 4 cent and 5 cent stamps.
Proof
Let P(n)  n cents can be formed using only 4 and 5 cent
P(n)  n = 4s + 5t s  0, and t  0  n  12
Basis : P(12) is true, since 12 = 4  3;
P(13) is true, since 13 = 4  2 + 5  1;
P(14) is true, since 14 = 4  1 + 5  2;
P(15) is true, since 15 = 5  3;
Inductive : Assume P(12), P(13), …, P(k) are true.
Now prove for P(k + 1) (k-3  12)
Suppose k-3 = 4  s + 5  t.
Then k +1 = 4  (s + 1) + 5  t. true for n = k + 1.
By Strong Induction, P(n) is true if n  Z and n 12.
Proving a Property of a Sequence
Proposition:
Suppose a0, a1, a2, … is defined as follows:
a0 = 1, a1 = 2, a2 = 3,
ak = ak-1 + ak-2 + ak-3 for all integers k ≥ 3.
Then an ≤ 2n for all integers n≥0. P(n)
Proof (by strong induction)
Basis step:
The statement is true
for n = 0: a0 = 1 ≤ 1 = 20 P(0)
for n = 1: a1 = 2 ≤ 2 = 21 P(1)
for n = 2: a2 = 3 ≤ 4 = 22 P(2)
Proving a Property of a Sequence
Inductive step:
For any k > 2, assume P(i) is true for all i with 0 ≤ i < k, i.e.,
ai ≤ 2i for all 0 ≤ i < k (1)
Show that
P(k) is true: ak ≤ 2k (2)
Now consider
ak = ak-1 + ak-2 + ak-3
≤ 2k-1 + 2k-2 + 2k-3 based on (1)
≤ 20 + 21 + … + 2k-3 + 2k-2 + 2k-1
= 2k - 1 ≤ 2k
Thus, P(n) is true by strong mathematical induction.
Hence it proves the result
Existence of Binary Integer Representation
Theorem
Given any positive integer n, there exists a unique representation of
n in the form:
n = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
Where r is non-negative integer
cr.= 1, and cj = 0 or 1,  j = 0, 1, 2, . . . , r-1
Proof (by strong induction)
Let P(n) be the statement that n can be written in the form
n = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
Basis step:
If n = 1, then n = cr.2r = c0, where r = 0, and c0 = 1
Hence the statement is true for n = 1, i.e. P(1) is true
Existence of Binary Integer Representation
Inductive Hypothesis:
Let us suppose that statement is true for all i, 1 ≤ i < k,
i = ck.2k + ck-1.2k-1 + . . . + c1.21 + c0
cr.= 1, and cj = 0 or 1,  j = 0, 1, 2, . . . , r-1
Show that
Now we prove that statement is true for k
Case 1
Suppose k is even, k/2 is an integer and k/2 < k, hence
k/2 = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
where r is non-negative integer and
cr.= 1, and cj = 0 or 1,  j = 0, 1, 2, . . . , r-1
Existence of Binary Integer Representation
k = 2.cr.2r + 2.cr-1.2r-1 + . . . + 2.c1.21 + 2.c0
k = cr.2r+1 + cr-1.2r + . . . + c1.22 + c0.21, true
which is the required form
Case 2
Let k ≥ 3, is odd, (k-1)/2 is an integer and 1 ≤ (k-1)/2 < k,
(k-1)/2 = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
where r is non-negative integer and
cr.= 1, and cj = 0 or 1,  j = 0, 1, 2, . . . , r-1
Now, k – 1 = cr.2r+1 + cr-1.2r + . . . + c1.22 + c0.21
And, k = cr.2r+1 + cr-1.2r + . . . + c1.22 + c0.21 + 1, true
Hence by strong mathematical induction, P(n) is true
Uniqueness
Uniqueness
Now we prove that n has a unique representation
n = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0
Where r is non-negative integer
cr.= 1, and cj = 0 or 1,  j = 0, 1, 2, . . . , r-1
On contrary, suppose that n has two different representations,
i.e.
n = cr.2r + cr-1.2r-1 + . . . + c1.21 + c0 (1) and
n = br.2r + br-1.2r-1 + . . . + b1.21 + b0 (2)
Now subtract (2) from (1) we get
0 = (br- cr)2r + (br-1- cr-1).2r-1 + . . . + (b0- c0) 
br = cr, br-1= cr-1, . . ., b1 = c1.and b0 = c0 , proved
More Complicated Example
1
Problem
Let f0 ( x ) = , and fn +1 = f0 fn , n  0.
2- x
Find an expression for fn and prove it by induction.
Solution
1
Since f 0 = and f n +1 = f o  f 0 therefore
2- x
1 1 2- x
f1 ( x) = f 0  f 0 (x) = f 0 ( )= =
2- x 2-
1 3 - 2x
2- x
2- x 1 3 - 2x
And, f 2 ( x) = f 0  f1 (x) = f 0 ( )= =
3 - 2x 2 - x 4 - 3x
2-
3 - 2x
More Complicated Example
3 - 2x
And, f 3 ( x) = f 0  f 2 (x) = f 0 ( )
4 - 3x
1 4 - 3x
= =
3 - 2x 5 - 4x
2-
4 - 3x

And so on n - (n - 1) x
f n ( x) = f 0  f n -1 (x) = f 0 ( )
(n + 1) - nx
1 (n + 1) - nx
= =
n - (n - 1) x (n + 2) - (n + 1) x
2-
(n + 1) - nx
More Complicated Example
Now generalized function is

(n + 1) - nx
f n ( x) =
(n + 2) - (n + 1) x

Now we prove this guess by mathematical Induction


Basis case: take n = 0
1
f0 = , which is true
2- x
(k + 1) - kx
f k ( x) =
(k + 2) - (k + 1) x
Inductive hypothesis: assume that statement is true n = k
More Complicated Example
Claim: Now we have to prove that statement is true n = k + 1
(k + 1 + 1) - (k + 1) x (k + 2) - (k + 1) x
f k +1 ( x) = =
(k + 1 + 2) - (k + 1 + 1) x (k + 3) - (k + 2) x

f n+1 = f 0  f n  f k +1 = f 0  f k k  0
By definition:
(k + 1) - kx 1
f k +1 ( x) = f 0 ( )=
(k + 2) - (k + 1) x (k + 1) - kx
2-
(k + 2) - (k + 1) x

(k + 2) - (k + 1) x
After simplifica tion, f k +1 ( x) = , proved.
(k + 3) - (k + 2) x

You might also like